2023
DOI: 10.1039/d3nr04062c
|View full text |Cite
|
Sign up to set email alerts
|

Robust superhydrophobic silicone/epoxy functional coating with excellent chemical stability and self-cleaning ability

Weidong Huang,
Xiaoli Jiang,
Yagang Zhang
et al.

Abstract: This study reports on the design and synthesis of a highly transparent fluorinated silicone resin with low surface energy, and its application in the preparation of superhydrophobic coatings with remarkable self-cleaning and robust performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…The organic solvent resistance of the Binder/ChNFs/Mosil coating could be ascribed to the stable chemical bonds of the silicon oxide chains in the Mosil layer. 36 As shown in Figure 7d, the Binder/ChNFs/Mosil coating maintained superhydrophobic with water contact angles above 150°and water sliding angles were about 13°until the pH increased to 10. The transmittance of a glass slide with the Binder/ChNFs/Mosil coating at 550 nm was 94.3% after immersion in the alkali solution with a pH of 12 for 30 min.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The organic solvent resistance of the Binder/ChNFs/Mosil coating could be ascribed to the stable chemical bonds of the silicon oxide chains in the Mosil layer. 36 As shown in Figure 7d, the Binder/ChNFs/Mosil coating maintained superhydrophobic with water contact angles above 150°and water sliding angles were about 13°until the pH increased to 10. The transmittance of a glass slide with the Binder/ChNFs/Mosil coating at 550 nm was 94.3% after immersion in the alkali solution with a pH of 12 for 30 min.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…The data in Figure a–c showed that the decrease in transmittance of the specimens was not significant and the coating surface still remained superhydrophobic with a water contact angle larger than 150° and a sliding angle lower than 10° after immersing in n -hexane, ethanol, or even DMSO for 180 min. The organic solvent resistance of the Binder/ChNFs/Mosil coating could be ascribed to the stable chemical bonds of the silicon oxide chains in the Mosil layer . As shown in Figure d, the Binder/ChNFs/Mosil coating maintained superhydrophobic with water contact angles above 150° and water sliding angles were about 13° until the pH increased to 10.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation